Acute drug‐induced immune thrombocytopenia ‐ A work of articaine. Issue 5 (19th March 2022) - Lægreid, Ingvild Jenssen; Olsen, Mats Irgen; Harr, Jon Inge; Grønli, Renathe Henriksen; Mørtberg, Trude Victoria; Ernstsen, Siw Leiknes; Ahlen, Maria Therese
Abstract: Background: Drug‐induced immune thrombocytopenia (DITP) is a rare, but serious complication to a wide range of medications. Upon suspicion, one should do a thorough clinical evaluation following proposed diagnostic criteria and seek laboratory confirmation. If confirmed, it is important to ensure avoidance of the drug in the future. Study design and methods: Herein, we describe a young adult male who experienced two bouts of severe thrombocytopenia following dental treatment. The thrombocytopenia was acknowledged due to unexpected hemorrhaging during the procedures. On both occasions, he was exposed to four different drugs, none commonly associated with DITP. After the second episode of severe procedural‐related thrombocytopenia, an investigation into the cause was initiated. We describe the clinical approach to elucidate which of the four implicated drugs was responsible for thrombocytopenia and the laboratory work‐up done to confirm that the reaction was antibody‐mediated and identify the antibody's drug: glycoprotein specificity. An alternative drug was tested both in vivo and in vitro, to identify an option for future procedures. Results: Sequential exposure revealed the local anesthetic substance articaine to induce thrombocytopenia. Laboratory work‐up confirmed drug‐dependent antibodies (DDAbs) with specificity for the glycoprotein Ib/IX complex, swiftly identified by a bead‐based Luminex assay. Further investigations by monoclonal antibody immobilization of platelet antigens assay (MAIPA) revealed a probable GPIb binding site. An alternative local anesthetic, lidocaine, was deemed safe for future procedures. Conclusion: Articaine can induce rapid‐onset, severe immune‐mediated thrombocytopenia causing bleeding complications. A modified bead‐based Luminex platelet antigen assay proved a useful addition in the DITP‐investigation.